Do Relaxin Levels Impact Hip Injury Incidence in Women? A Scoping Review - Parker, Emily A.; Meyer, Alex M.; Goetz, Jessica E.; Willey, Michael C.; Westermann, Robert W. (Frontiers in Endocrinology, 2022)
Purpose: The aim of this review is to assess the current evidence regarding the impact of relaxin on incidence of soft tissue hip injuries in women. Methods: A trained research librarian assisted with searches of PubMed, Embase, CINAHL, and SPORTDiscus, with a preset English language filter. The review was completed per the Joanna Briggs Institute (JBI) Manual for Evidence Synthesis methodology. Included studies required assessment of relaxin effects on musculoskeletal health, pelvic girdle stability, or hip joint structures in human subjects. Letters, texts, and opinion papers were excluded. Results: Our screen yielded 82 studies. Molecularly, relaxin activates matrix metalloproteinases (MMPs) including collagenases MMP-1/-13 and gelatinases MMP-2/-9 to loosen pelvic ligaments for parturition. However, relaxin receptors have also been detected in female periarticular tissues, such as the anterior cruciate ligament, which tears significantly more often during the menstrual cycle peak of relaxin. Recently, high concentrations of relaxin-activated MMP-9 receptors have been found on the acetabular labrum; their expression upregulated by estrogen. Conclusions: Menstrual cycle peaks of relaxin activate MMPs, which locally degrade collagen and gelatine. Women have relaxin receptors in multiple joints including the hip and knee, and increased relaxin correlates with increased musculoskeletal injuries. Relaxin has paracrine effects in the female pelvis on ligaments adjacent to hip structures, such as acetabular labral cells which express high levels of relaxin-targeted MMPs. Therefore, it is imperative to investigate the effect of relaxin on the hip to determine if increased levels of relaxin are associated with an increased risk of acetabular labral tears.